Problems of government regulation of gambling as a source of income of the national budget - Olga Nikolayeva (Cхід, 2013)
In the article the questions of expediency of the resumption of gambling to replenish the state and local budgets are considered. The focus is on assessing changes in legislation to regulate business activities in the field of entertainment. The dynamics of the issued, updated licenses to organize and conduct games of chance and patents for the realization of operations to provide services in this area is shown. Besides, the indicators of incoming taxes on particular articles of the State Budget of Ukraine are shown. Conclusions about the need of state regulation of gambling and order of funds transfer from licensing or sale of commercial patent are made.